(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрены некоторые тенденции развития рельсового транспорта (в контексте общего пространственного развития) в городах, сравнимых с Пермью по численности населения или (и) территориальной структуре. Даны предложения по корректировке подходов к развитию транспортной инфраструктуры, предусмотренных Генеральным планом г. Перми. DEVELOPMENT OF URBAN RAILWAY TRANSPORT IN PERM CITY Some tendencies of Light Rail Transport System development in cities, which are compared with Perm by population and territorial structure (in context of common space development), are considered. Proposals for correction of approaches to transport infrastructure development, offered by the general plan of Perm City, are given.